2015
DOI: 10.1007/s00167-015-3538-3
|View full text |Cite
|
Sign up to set email alerts
|

Poor osteochondral repair by a biomimetic collagen scaffold: 1- to 3-year clinical and radiological follow-up

Abstract: Prospective therapeutic study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 28 publications
9
99
0
2
Order By: Relevance
“…[95] However, a recent study reported inconsequential osteochondral recovery using this biomimetic scaffold. [92] Additionally, a major ambiguity in these studies is the absence of gold standards, therefore, no comparisons are made through controls. More recently, another approach for cartilage regeneration was explored using a decellularized cartilage based scaffold.…”
Section: Nanoengineered Bone-cartilage Interfacementioning
confidence: 99%
“…[95] However, a recent study reported inconsequential osteochondral recovery using this biomimetic scaffold. [92] Additionally, a major ambiguity in these studies is the absence of gold standards, therefore, no comparisons are made through controls. More recently, another approach for cartilage regeneration was explored using a decellularized cartilage based scaffold.…”
Section: Nanoengineered Bone-cartilage Interfacementioning
confidence: 99%
“…Natural biological materials, such as collagen and fibrin, are promising candidate scaffolds for cartilage engineering [15,16] as they play multiple key roles in structural maintenance of the defect shape and void volume for vascularization, and serve as temporary extracellular matrix for cell adhesion, proliferation, differentiation, and maturation [17,18]. Collagen scaffolds have been actively used in research as well as in clinical applications for meniscus and osteochondral defect regeneration [19]. The most widely used collagen in biomedical applications is collagen type I that provides a welcoming microenvironment for chondrocytes to produce extracellular matrix [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Delcogliano and colleagues [39] reported a significant improvement of the evaluated clinical parameters (International Repair Cartilage Society score, the Tegner Score and EQ-VAS). The significant clinical improvements were confirmed by Christinseen et al [40] that however reported an incomplete cartilage repair and poor subchondral bone repair at 1-and 2.5-year follow-up by treatment of osteochondral defects in the ankle and knee joint with the graded biomimetic scaffold MaioRegen®.…”
Section: Bone-like Scaffolds: Bioceramic and Nano-composite Monolithimentioning
confidence: 53%